Optimizing the production technology of eco-friendly foam polyurethane panels on the continuous line - Phung Xuan Son; Vu Thi Hue; Mai Duc Thuan; Nguyen Minh Quang; Nguyen Duy Trinh (Vietnam Journal of Science and Technology, 2023)
With the preeminent features of polyurethane (PU) panels such as sound insulation, heat insulation, fireproof, high load capacity, lightweight, high aesthetics, especially using simple and easy assembly construction and move, so new PU panel is now the first choice for construction projects. In this work, the authors study the new generation physical foaming agent cyclopentane that is environmentally friendly and completely does not destroy the ozone layer. Study investigating and evaluating the effect of content of physical foam cyclopentane on free expansion density, reaction time of rigid polyurethane foam (R-PUF), and reaction time values ​​(cream time, gel time, tack-free time, and rise time). The morphology and size of the closed-cell of the R-PUF samples with cyclopentane concentrations increasing from 0% to 20% are observed by the optical microscope image and the closed-cell size distribution chart is determined by IT3 software. In addition, the physical and mechanical properties of dimensional stability and compressive strength were analyzed to evaluate the quality of the expanded R-PUF insulation in the mold using a cyclopentane physical foaming agent. Experimental procedures according to Taguchi’s analysis on the continuous production line are aimed at giving optimal parameters for the industrial PU panel manufacturing process. The research results provide an excellent reference value for manufacturers to further improve the performance and quality of PU panels.